Spatial Clustering of Housing Backlog and Socioeconomic Inequality: Evidence from the Special Region of Yogyakarta - Fahril Fanani; A. Yunastiawan Eka Pramana; Ayu Candra Kurniati (Jurnal Permukiman, 2026)
Housing backlog remains a critical challenge in Indonesia, particularly for low-income communities. However, existing mitigation policies often rely on aggregate data, overlooking the spatial concentration of poverty and housing needs. This study investigates the spatial clustering of housing backlogs and its correlation with socioeconomic status in the Special Region of Yogyakarta. Utilizing a quantitative spatial approach, the study employs Global Moran’s I and Local Indicators of Spatial Association (LISA) to diagnose geographic disparities. The analysis reveals a significant positive spatial autocorrelation (Moran's I = 0.643), identifying distinct "hotspots" where high housing deficits significantly overlap with low socioeconomic clusters. Unlike conventional descriptive studies, these findings demonstrate that housing vulnerability is not randomly distributed but structurally trapped in specific zones. The study concludes that "one-size-fits-all" subsidies are insufficient and advocates for spatially targeted interventions to address these entrenched inequalities effectively.